DESAIN BIOREAKTOR PENGOLAHAN LIMBAH AIR ASAM TAMBANG MENGGUNAKAN SEDIMEN WETLAND SEBAGAI SUMBER INOKULUM MIKROBA BAKTERI PEREDUKSI SULFAT - Arnol Arnol (Hasanuddin Student Journal, 2018)
Acid  mine drainage is one of the dangerous  wastes produced by mining activities because it contains sulfuric acid and heavy metals of high grade. This study aims to determine the influence of mangrove sediments in reducing heavy metals, increasing pH, reducing levels of sulphate and increasing the number of microbes. The results showed that the distribution of mangrove sediments in the treatment of P1, P2 and P3 on AMD could increase the pH of AMD successively from 2,22, 2,14 and 2,16 to 7,21,7,22 and 7,13 after 30 day. Mangrove sediment was also able to reduce sulphate concentration from sulphate concentration at AMD within 30 days from level of 383,25 ppm, 408,34 ppm and 405,15 ppm to 225,51 ppm, 181,34 ppm and 211 , 32 ppm. Mangrove sediment was able to decrease Pb, Cu, Fe metal content on the first day as much 1.5493 ppm, 1.87 ppm and 2.20 ppm to 0 ppm, 0.0431 ppm and 1.2231 ppm. The study also showed that the amount of microbes in the sediments continued to increase on the 30th day 1.2 x 1012 CFU / mL, 1.9 x 1012 CFU / mL and 4.6 x 1010 CFU / mL.